Orbital fat prolapse in a Persian cat. Case report - Laus, J. L.; Ortiz, JPD; Carneiro, APM; Lisbao, CBS (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2005)
A two and a half-year-old female Persian cat was presented with a history of bilateral chronic ocular discharge. Epiphora bilateral mucous ocular discharge and a volume increase in bulbar conjunctiva on the dorsolateral quadrant of the right eye were noticed during routine ophthalmic examination. Ophthalmic examination and the aspiration cytology showed the presence of adipose tissue at the right eye dorsolateral quadrant indicating orbital fat prolapse.
Keywords: Cat; eye; Solos - Preparo